PENGARUH KOMBINASI PUPUK ANORGANIK, ORGANIK DAN MULSA JERAMI PADI TERHADAP PERTUMBUHAN DAN HASILâ BAWANG MERAH VARIETAS LEMBAH PALU â DI DESA OLOBOJU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Silvani, Silvani; Yusuf, Ramal; Syakur, Abd. (AGROTEKBIS, 2016)
The purpose of this study is to examine the best combination ofÂ anorganic fertilizers, organic and mulch on onion Lembah Palu varieties growth and yield. This study used a randomized block design. The treatment were anorganic fertilizer, organic and mulch consisting of 7 combinations. Each treatment consisted of 4 groups so that there were 28 experiments units. Application of anorganic fertilizers, organic and rice straw mulch showed no effect on plant growth parameter such as plant heigt and number of leaves. The highest plant fresh weight were in the treatment of organic fertilizer and rice straw mulch (65.89 g), the highest number of tubers in the treatment of anorganic fertilizers, organic and rice straw mulch (8:15 g), the highest leaf weight in treatment of organic fertilizer and rice straw mulch (33.39 g), the highest root weight on anorganic fertilizer treatment (4.91 g) and the highest weight of tubers in the treatment of anorganic fertilizers, organic and rice straw mulch (29.57 g) .Â Key Words : Anorganic fertilizer, Onion, organic, rice straw mulch.